2019
DOI: 10.1016/j.drugalcdep.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cocaine administration upregulates FKBP5 in the extended amygdala of male and female rats

Abstract: Background: Dysregulation of glucocorticoid receptors has been implicated in addiction and stress-related disorders. FKBP5 is a co-chaperone of the glucocorticoid receptor and regulates receptor sensitivity. While FKBP5 is known to be involved in mood-and stress-related disorders, less is known regarding FKBP5 and cocaine abuse. This study investigated the regulation of FKBP5 expression in the extended amygdala and paraventricular nucleus of the hypothalamus, regions important in the control of stress-response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the past several years, there has been a shift toward systematically studying sex differences in preclinical addiction models. Recent studies have identified sex differences in mRNA and protein expression in stress systems and glutamatergic signaling pathways within the reward circuitry following cocaine exposure ( Connelly and Unterwald, 2019 , 2020 ; Castro-Zavala et al, 2020 ). Such studies will lay the foundation for future work focused on identifying cellular and synaptic mechanisms driving sex differences in behavioral responding to cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years, there has been a shift toward systematically studying sex differences in preclinical addiction models. Recent studies have identified sex differences in mRNA and protein expression in stress systems and glutamatergic signaling pathways within the reward circuitry following cocaine exposure ( Connelly and Unterwald, 2019 , 2020 ; Castro-Zavala et al, 2020 ). Such studies will lay the foundation for future work focused on identifying cellular and synaptic mechanisms driving sex differences in behavioral responding to cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also showed that genetic variants on CX3CR1 were associated with HIV susceptibility and rapid HIV progression to AIDS [79]. cg25114611, located in the promoter region of FKBP5, is also biologically plausible, given the implication for chronic cocaine administration upregulating FKBP5 expression in rats [80].…”
Section: Discussionmentioning
confidence: 99%
“…12 It also appears that the extended amygdala, which influences the hypothalamic-pituitary-adrenal (HPA) axis, a key component in the stress response, is altered with chronic substance use. 15 Researchers believe elevated levels of a FKBP5 protein in the extended amygdala, as seen in rats following chronic cocaine use, 15 may lead to a loss of negative feedback yielding overactivity of the HPA axis, 16 resulting in more severe negative affective symptoms of cocaine withdrawal. 15 This may lead to an increased drive for relapse.…”
Section: Introductionmentioning
confidence: 99%
“…15 Researchers believe elevated levels of a FKBP5 protein in the extended amygdala, as seen in rats following chronic cocaine use, 15 may lead to a loss of negative feedback yielding overactivity of the HPA axis, 16 resulting in more severe negative affective symptoms of cocaine withdrawal. 15 This may lead to an increased drive for relapse. 15 While these studies illustrate the nature of the brain's response to substances of abuse, others demonstrate how long these effects last.…”
Section: Introductionmentioning
confidence: 99%